Tolerance as a Foundation of Mental Health among Indonesian Youth in the Digital Era: The Role of Multicultural Intelligence and Cross-Ethnic and Interreligious Friendship - Huwae, Arthur; Ristanti, Clara Bonita Dinar; Winantu, Dyah Widhi; Pramudianti, Rebecca; Pongdatu, Laurenzia Putri Salo; Kiranadevi, Safira Yuniar; Yuliana, Alya Inas (Scidacplus, 2026)
The digital era presents both challenges and potential threats to the sustainability of local cultural values in Indonesia. Rapid developments in information technology have contributed to shifts in traditional wisdom, which in some cases are marked by an increased tendency toward intolerance. Such phenomena have the potential to damage national identity and disrupt social harmony in a multicultural society. From a psychological perspective, intolerance can be mitigated through the enhancement of cognitive understanding of diversity via multicultural intelligence, as well as the realization of prosocial behavior through the development of cross-ethnic and interreligious friendships. Therefore, this study aims to examine the role of multicultural intelligence and cross-ethnic and interreligious friendships as predictors of tolerance among university students in the digital era. A quantitative approach with a multiple linear regression design was employed. The study involved 1,038 students from diverse ethnic and religious backgrounds, selected using a convenience sampling technique. The research instruments included the Cultural Intelligence Scale, the Cross-Ethnic and Interreligious Friendship Scale, and the Tolerance Scale. The results indicated that multicultural intelligence and cross-ethnic and interreligious friendships significantly predicted tolerance (F = 633.814, p < 0.01). These findings suggest that tolerance can be cultivated through enhancing individuals’ understanding of diversity and through positive social interactions with people from different ethnic and religious backgrounds. The implications of this study emphasize the importance of implementing educational programs based on cross-ethnic, interreligious, and cultural literacy within academic environments on a continuous basis. Such programs are expected to support young people in consistently internalizing and practicing tolerance in diverse social contexts.